A geospatial approach to uncovering the hidden waste footprint of Lake Superior's Mesabi Iron Range. Issue 4 (November 2016) - Baeten, John; Langston, Nancy; Lafreniere, Don
Abstract: For decades, the Lake Superior Iron District produced a significant majority of the world's iron used in steel production. Chief among these was the Mesabi Range of northern Minnesota, a vast deposit of hematite and magnetic taconite ores stretching for over 100 miles in length. Iron ore mining in the Mesabi Range involved three major phases: direct shipping ores (1847–1970s), washable ores (1907–1980s), and taconite (1947–current). Each phase of iron mining used different technologies to extract and process ore. Producing all of this iron yielded a vast landscape of mine waste. This paper uses a historical GIS to illuminate the spatial extent of mining across the Lake Superior Iron District, to locate where low-grade ore processing took place, and to identify how and where waste was produced. Our analysis shows that the technological shift to low-grade ore mining placed new demands on the environment, primarily around processing plants. Direct shipping ore mines produced less mine waste than low-grade ore mines, and this waste was confined to the immediate vicinity of mines themselves. Low-grade ore processing, in contrast, created more dispersed waste landscapes as tailings mobilized from the mines themselves into waterbodies and human communities.